Tajikistan Risk and Resilience Assessment - World Bank (World Bank, Washington, DC, 2019)
Tajikistan was ill-equipped for independence in 1991, and slipped almost immediately into violence. The civil war ended in 1997 with a peace accord that, thanks to a power sharing agreement, was able for a few years to ensure a degree of peaceful political competition. In recent years, political instability and the potential for violence in Tajikistan has grown with pervasive governance challenges, include elite capture of political and economic power, high-level corruption, and the closing of political space. Political and security challenges exacerbate, and are exacerbated by, economic, social, and cross-border risks. Indeed, most global indices that examine fragility and conflict place Tajikistan in a category of elevated risk. This risk and resilience assessment (RRA) is intended to provide a comprehensive understanding of the fragility, conflict, and violence (FCV) stresses facing Tajikistan and the potential role of the Bank in helping to address these risks. Report is organized as follows: chapter one gives introduction. Chapter two of the provides an overview of Tajikistan’s geography, demography, and economy and discusses the historical context that has led to Tajikistan’s current challenges. Chapter three provides an overview of the priority risks - political and security, economic, inclusion and regionalism, and cross-border and global that increase Tajikistan’s vulnerability to violence and instability. Chapter four discusses the specific triggers or scenarios that can destabilize the status quo or lead to widespread unrest. Chapter five identifies sources of resilience the World Bank Group (WBG) may wish to consider and build upon. Chapter six concludes with suggested recommendations to the WB on the way forward.